Corrected integrated density: a novel method for liver elastic fibers quantification in chronic hepatitis C - Carine Leite; Rodrigo Tzovenos Starosta; Eduardo Neubarth Trindade; Manoel Roberto Maciel Trindade; Mário Reis Álvares-; Carlos Thadeu Schmidt Cerski (BMC, 2020)
Abstract Background Elastic fibers deposition is triggered during liver fibrosis and is related to worse clinical prognosis in chronic hepatitis C patients. This study aimed to verify if a new method for elastic fiber quantification can be used to discriminate between different degrees of fibrosis in liver biopsies of patients with hepatitis C. Methods Individuals presenting with different degrees of fibrosis in liver biopsy were included. Slides of liver samples were stained with orcein with and without prior oxidation. Morphometric analysis was proceeded, and quantification accomplished by corrected integrated density. Results Twenty-seven patients, mean age 52 years-old, 59% women, were included. Elastic fibers density was higher in advanced fibrosis patients and there was a positive correlation with Metavir score (Spearman r = 0.609, p < 0.001), as well as with the noninvasive scores Fib-4 (Pearson r = 0.46, p = 0.029) and APRI (r = 0.52, p = 0.01). Conclusion Morphometric analysis by corrected integrated density demonstrates that elastic fibers abundance is higher in advanced stage of fibrosis in patients with hepatitis C.